47.2k views
3 votes
In the equation, 4x + 14 = - 2x - 22 + 12 what is one of the steps that should be taken to solve for x?

User Cliff AB
by
5.9k points

1 Answer

7 votes

Answer:

First step: Combine like terms on each side of the equation

See below for the rest of the steps

Explanation:

First step: Combine like terms on each side of the equation

4x + 14 = -2x - 22 + 12

4x + 14 = -2x - 10

Second step: Get the variables on one side, and get the constants on the other

4x + 2x = -10 - 14 (add 2x to, and subtract 14 from both sides of the equation)

Third step: combine like terms again

6x = -24

Fourth step: Solve for x

x = -4 (divide by 6 on both sides)

User Halexh
by
6.0k points